Analysis of the Phytochemical Composition of Papaya Root (Carica papaya L.) and Its Potential as an Anticarcinogenic Agent: A Preliminary Study - Shabila Rizka Azzahra; Elman Boy; Yulia Afrina Nasution (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Cancer remains a major global health problem with high morbidity and mortality. Conventional treatments often cause serious side effects and require high costs, encouraging the exploration of natural products as alternative anticarcinogenic agents. Carica papaya L. contains various secondary metabolites, but studies on its root are still limited. Objective: This study aimed to conduct phytochemical screening and simplicia characterization of papaya root (Carica papaya L.) and preliminarily assess its potential as an anticarcinogenic agent. Methods: This descriptive laboratory study used an exploratory approach. Papaya roots were processed into simpliciathrough drying, grinding, and sieving, followed by ethanol maceration. Simplicia characterization included moisture content, total ash, acid-insoluble ash, and water- and ethanol-soluble extractive values. Phytochemical screening was conducted using specific reagents to identify secondary metabolites. Results: The results showed that papaya root contained glycosides, saponins, and triterpenoids/steroids, while alkaloids, flavonoids, and tannins were not detected. The highest characterization value was water-soluble extractives at 19.38%, while acid-insoluble ash was the lowest at 5.07%, indicating relatively good simplicia quality. Conclusion: Papaya root contains secondary metabolites with potential anticarcinogenic relevance. Further in vitro and in vivo studies are required to confirm its pharmacological activity.